EFFECT OF WORK ON CONSUMER INTERNET USE (CASE STUDY IN THE REGION JOGJAKARTA, BANTUL, SLEMAN, Kulonprogo, AND GUNUNGKIDUL) - PRATOMO, ARIEF BUDI (Management, 2010)
Internet is one of the most sophisticated information technology in this century, so as to improve the quality of human resources quality at high especially for island nations such as Indonesia. The need for socialization of education about Internet technology that began at an early age so that people can understand about information technology. If one consumer is not satisfied on the Internet is very expensive leases are held by Internet service companies, the companies will be able to easily Internet services became popular, which means it can bankrupt the company. Type of work in accordance with these educational levels of employees more often cause a person to access the internet to obtain a wide range of accurate and current information as well as various convenience in communicating to assist the smooth work of a person in a company where he works .. Keyword : Internet, Work, Information Technology